2005
DOI: 10.1136/ard.2003.018705
|View full text |Cite
|
Sign up to set email alerts
|

Up regulated expression of fractalkine/CX3CL1 and CX3CR1 in patients with systemic sclerosis

Abstract: Background: Fractalkine expressed on endothelial cells mediates activation and adhesion of leucocytes expressing its receptor, CX 3 CR1. Soluble fractalkine exhibits chemotactic activity for leucocytes expressing CX 3 CR1. Objective: To determine the role of fractalkine and its receptor in systemic sclerosis (SSc) by assessing their expression levels in patients with this disease. Methods: The expression of fractalkine and CX 3 CR1 in the skin and lung tissues was immunohistochemically examined. Circulating so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
67
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 38 publications
(13 reference statements)
4
67
1
Order By: Relevance
“…Multiple reparative processes were affected by the receptor, including inflammation, fibrosis, neovascularization, and regeneration of parenchymal cells. The results are consistent with previous reports showing that the CX3CL1-CX3CR1 ligand-receptor pair plays an important role in the initiation and progression of inflammation (12)(13)(14), and is up-regulated in inflammatory diseases (20 -23, 26, 27, 42), including inflammatory diseases of the skin (15,16,19). Our data linking CX3CR1 to fibrosis in skin wound healing are consistent with a report of CX3CL1 and CX3CR1 expression in the skin and lung of patients with systemic sclerosis (16), and an in vivo study showing that CX3CR1 KO mice have reduced collagen accumulation and renal fibrosis in a model of ischemia-reperfusion injury (18).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Multiple reparative processes were affected by the receptor, including inflammation, fibrosis, neovascularization, and regeneration of parenchymal cells. The results are consistent with previous reports showing that the CX3CL1-CX3CR1 ligand-receptor pair plays an important role in the initiation and progression of inflammation (12)(13)(14), and is up-regulated in inflammatory diseases (20 -23, 26, 27, 42), including inflammatory diseases of the skin (15,16,19). Our data linking CX3CR1 to fibrosis in skin wound healing are consistent with a report of CX3CL1 and CX3CR1 expression in the skin and lung of patients with systemic sclerosis (16), and an in vivo study showing that CX3CR1 KO mice have reduced collagen accumulation and renal fibrosis in a model of ischemia-reperfusion injury (18).…”
Section: Discussionsupporting
confidence: 82%
“…Recently, a profibrotic activity has been suggested for CX3CL1/CX3CR1 based on the finding that patients with systemic sclerosis have increased expression of CX3CL1 and increased CX3CR1 ϩ leukocytes in fibrotic skin and lung lesions (16). Moreover, bone marrow (BM) 3 cells are known to play important roles in multiple organs in repair/regeneration of injured tissues, through a complex interplay between adhesion molecules, cytokines, and chemokines (3,24,25), and CX3CR1 is expressed on most monocytes/macrophages (16 -18, 21, 23).…”
mentioning
confidence: 99%
“…Chemokines, which also have conserved cysteine motifs, and their receptors, are essential components of Th1-and Th2-mediated responses (43). Moreover, chemokine levels are increased in the serum and BAL of patients with SSc-associated pulmonary fibrosis (44,45). Recently, up-regulated expression of CCL11 was reported to induce fibrosis (46).…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] Recently, patients with systemic sclerosis were reported to have increased serum levels of fractalkine and increased CX3CR1 ϩ macrophages and T cells in fibrotic skin and lung. 19 These data have suggested that fractalkine/CX3CR1 may promote tissue fibrosis through inflammatory cell infiltration. Here we test this hypothesis in a mouse model of ischemia-reperfusion injury of the kidney.…”
mentioning
confidence: 99%